Understanding the phenomenon «image» in the humanities - Zharkova, Alina V. (Journal of the Belarusian State University. Philology, 2025)
The issue of analysing the concept «image», which is ambiguously interpreted in linguoculturology, is considered. An analytical review of the most significant studies dedicated to this phenomenon is conducted. The ontology of its development is described. The search for the most relevant definitions of the term «image» is carried out. The substantive and structural components of this concept are analysed, and its main characteristics are identified and revealed (including from the perspective of its representation in Russian-language linguoculture). The purposeful nature of image modelling, which implies a selective approach to defining the qualities necessary to achieve specific communicative tasks and a reliance on the potential audience, is emphasised. It is established that the primary function of the phenomenon «image» is communicative function.
Keywords: linguistic personality; concept «image»; image carrier; communicative function; dynamism